2012
DOI: 10.1017/s0003055412000317
|View full text |Cite
|
Sign up to set email alerts
|

Competing for Liberty: The Republican Critique of Democracy

Abstract: Freedom as non-domination has acquired a leading status in political science. As a consequence of its success, neo-roman republicanism also has achieved great prominence as the political tradition that delivered it. Yet despite the fact that liberty in the Roman mode was forged not only in direct confrontation with monarchy but against democracy as well, the relationship of republicanism to democracy is the great absentee in the contemporary debate on non-domination. This article brings that relationship back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 56 publications
(42 reference statements)
0
15
0
4
Order By: Relevance
“…Urbinati has already suggested that one sees in neo-Roman normative theory an "echo" of the Roman resistance to equality. 89 I am pointing to a slightly different, though related, aspect of neo-Roman approaches; namely, to their language of non-coercion, non-arbitrariness, non-domination, and consent. 90 Where Foucault is helpful is not just in alerting us to different sites of domination, but also in exploring how these forms of domination are normalized; how something that is arbitrary, for example, is seen as non-arbitrary.…”
Section: Reason and Right Actionmentioning
confidence: 99%
“…Urbinati has already suggested that one sees in neo-Roman normative theory an "echo" of the Roman resistance to equality. 89 I am pointing to a slightly different, though related, aspect of neo-Roman approaches; namely, to their language of non-coercion, non-arbitrariness, non-domination, and consent. 90 Where Foucault is helpful is not just in alerting us to different sites of domination, but also in exploring how these forms of domination are normalized; how something that is arbitrary, for example, is seen as non-arbitrary.…”
Section: Reason and Right Actionmentioning
confidence: 99%
“…Another, more recent theoretician who has also elaborated on the subject is Nadia Urbinati (Urbinati, ).…”
mentioning
confidence: 99%
“…For analyses regarding how this concept of equality relates to various forms of liberty, as well as different competing forms of equality, not least the competing neo‐roman republican approach, see Urbinati, . Arendt returns to the specific form of public judgement and how it is constitutive of political action; see Arendt, , , 2007.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of these types rule according to laws established in the general interest; rather they rule according to particular whims or desires. David Wootton reiterates this idea in his observation that the republic came to refer to 'a mixed form of government, where monarchy was prevented from degenerating into a tyranny, where popular power was prevented from degenerating into mob rule' (Wootton 1994: 6; see also Urbinati 2012).…”
mentioning
confidence: 99%